2020
DOI: 10.3892/ol.2020.12056
|View full text |Cite
|
Sign up to set email alerts
|

Systemic thromboembolism from a misdiagnosed non‑bacterial thrombotic endocarditis in a patient with lung cancer: A case report

Abstract: Thromboembolic events are frequent in patients with cancer, commonly involving the venous and pulmonary circulation. The arterial system is rarely implicated in embolism and, when involved, a cardiogenic origin should always be excluded. In the present study, a case of a patient who developed multiple embolic events concomitantly with the diagnosis of locally-advanced non-small cell lung cancer with high expression levels of programmed death-ligand 1 (PD-L1) in >50% of tumor cells is reported. A cardiac defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Two additional cases reported echocardiogram findings suggestive of infective endocarditis; one such case diagnosed NBTE of the mitral valve in a patient with known stage 4 malignancy [ 12 ]. Another case presented initially with acute deep venous thrombosis and pulmonary embolism with an incidentally identified lung mass; subsequently, this patient developed additional thrombotic events eventually leading to the diagnosis of NBTE of the mitral valve in the setting of large cell carcinoma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two additional cases reported echocardiogram findings suggestive of infective endocarditis; one such case diagnosed NBTE of the mitral valve in a patient with known stage 4 malignancy [ 12 ]. Another case presented initially with acute deep venous thrombosis and pulmonary embolism with an incidentally identified lung mass; subsequently, this patient developed additional thrombotic events eventually leading to the diagnosis of NBTE of the mitral valve in the setting of large cell carcinoma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…[20] Although the prognosis of cases diagnosed in recent years is more favorable in terms of survival, [20] numerous reports document instances of patient death before the initiation of cancer treatment. [21][22][23][24] A systematic review of 163 cases with newly diagnosed NBTE identified an in-hospital mortality rate of 30%. It further demonstrated that factors such as splenic infarction, renal infarction, pulmonary embolism, and mitral valve regurgitation (all present in the patient in our case) were among the factors associated with an increased risk of in-hospital mortality.…”
Section: Demonstrationmentioning
confidence: 99%
“…As is true with most neoplasms, lung cancer can have a variety of adverse effects on the body, including hypercoagulability, which can lead to thromboembolic events such as pulmonary emboli (PE), deep vein thrombosis (DVT), ischemic strokes, and non-bacterial thrombotic endocarditis (NBTE) [1][2][3]. Hypercoagulability due to cancer is, in part, due to an imbalance between factors that drive coagulation and fibrinolysis [4]. Cancer cells can release procoagulant factors such as tissue factor and thrombin, and there is often inflammation leading to the recruitment of proinflammatory cytokines such as tumor necrosis factorα (TNF-α) and interleukin-1 (IL-1) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Hypercoagulability due to cancer is, in part, due to an imbalance between factors that drive coagulation and fibrinolysis [4]. Cancer cells can release procoagulant factors such as tissue factor and thrombin, and there is often inflammation leading to the recruitment of proinflammatory cytokines such as tumor necrosis factorα (TNF-α) and interleukin-1 (IL-1) [4,5]. The production of these factors leads to a hypercoagulable state which promotes coagulation and thrombi formation [2].…”
Section: Introductionmentioning
confidence: 99%